Influence of cashew nut shell liquid on corrosion and tribocorrosion behavior of metallic alloys (2024)
Cashew Nut Shell Liquid (CNSL) has been explored in several applications within the sustainability principles and circular economy of agro-industrial product waste. To understand the anticorrosive and lubricant properties of CNSL solutions, a multi-faceted approach, incorporating electrochemical analyses, immersion test, tribological measurements, and tribochemical characterization was carried out for mild steel AISI 1012, stainless steel AISI 420 and Aluminium Alloy 6061. Electrochemical analyses reveal a positive impact of CNSL, inducing a shift in corrosion potential to more positive values and a decrease in corrosion current, indicating effective corrosion inhibition for stainless steel and aluminium alloy. In mild steel, CNSL exhibits a mixed-type inhibition with efficiency increasing in correlation with oil concentration. The lubricating properties of CNSL are evident according to the coefficients of friction (COF) obtained and the elastohydrodynamic lubrication regime observed during tribological tests. Tribochemical tests demonstrate a reduction in wear and an improvement in tribocorrosion behavior under sliding conditions. CNSL emerges as a promising tribocorrosion mitigator, demonstrating multifaceted benefits. The concentration-dependent effects highlight the need for optimization in specific applications, particularly for passive materials. CNSL not only inhibits corrosion through film formation but also provides effective lubrication, reducing friction, wear, and chemical-mechanical degradation. This research contributes valuable insights to corrosion science. It proposes practical applications for CNSL in diverse industrial contexts, showcasing its potential as an environmentally friendly and sustainable solution for tribocorrosion challenges.